Species checklist of Orthoptera (Insecta) from Sakaerat Environmental Research Station, Thailand (Southeast Asia) - Dawwrueng, Pattarawich; Tan, Ming Kai; Artchawakom, Taksin; Waengsothorn, Surachit (Zootaxa, 2017)
Sakaerat Biosphere Reserve is one of the four Biosphere Reserves in Thailand. It is situated at Khorat Plateau and comprises of mainly dry evergreen forest and dry dipterocarp forest. Despite studies that document its rich biodiversity, there was no concerted study on the orthopteran diversity. Recent sampling by the authors in Sakaerat led to the discovery of numerous undescribed species. A checklist, first for the place, is also reported here, each species represented with a habitus photograph. In total, 128 species of Orthoptera from 11 families were recorded. Caelifera (grasshoppers) were represented with five families and Ensifera (crickets and katydids) were represented with six families, making up 10 of the 16 lineages in the orthoptera phylogeny.